Pengaruh Disiplin dan Lingkungan Kerja Terhadap Kinerja Karyawan - Irma Sari Octaviani; Lidya Pricilla (CV. ULIL ALBAB CORP, 2024)
This study aims to analyze the influence of work discipline and work environment on employee performance at PT. Express Maximum Cabang Bandara Soekarno Hatta. Using a quantitative approach with an associative method, this study involved employees as respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that work discipline and work environment have a positive and significant impact on employee performance. Work discipline has a significant effect at the five percent significance level, while the work environment has a greater and very significant effect at the one percent significance level. The analysis indicates that both variables simultaneously have a significant impact on employee performance. This study emphasizes the importance of work discipline and work environment in enhancing employee performance. Therefore, it is recommended that the company develop consistent discipline programs and create a comfortable and supportive work environment. Implementing effective strategies in these two aspects is expected to help the company achieve organizational goals and increase employee satisfaction and productivity.